The Measurement of the Zakat Management Organization Transparency Index at Baznas Province - Jamaluddin, Inayah Auliannisa; Bahri, Efri Syamsul; Kamal, Mustafa (Yayasan Mitra Peduli Indonesia, 2024)
This research aims to measure and compare the transparency index at the provincial level of the National Board of Zakat Republic of Indonesia (BAZNAS). This research uses quantitative methods with a descriptive approach. The transparency index is measured using the Zakat Management Organization Transparency Index (ITRANS OPZ) model with a multi-stage weight index approach. Sample selection was based on purposive sampling, with four entities: BAZNAS South Kalimantan Province, BAZNAS Special Region of Yogyakarta, BAZNAS Bengkulu, and BAZNAS Southeast Sulawesi. The results of measuring the transparency index in four BAZNAS Provinces are sequentially as follows: BAZNAS Special Region of Yogyakarta (0.96), BAZNAS South Kalimantan, BAZNAS Southeast Sulawesi (0.89), and BAZNAS Bengkulu (0.81). The comparison results of four BAZNAS Provinces show that the highest index is BAZNAS South Kalimantan and BAZNAS Special Region of Yogyakarta (financial dimension; 0.40), BAZNAS South Kalimantan, BAZNAS Province Special Region of Yogyakarta, and BAZNAS Southeast Sulawesi (management dimension; 0.26), and BAZNAS Special Region of Yogyakarta (program dimension; 0.30). This research implies that BAZNAS, at the provincial level, needs to increase the transparency index to increase Muzaki's trust and collect zakat funds in each Province.